Предмет: Алгебра,
автор: maksimcelnokov7
3(2x-3)+7(1-2x)=1-2(x+4)
Ответы
Автор ответа:
1
Ответ:
x=5/6
Объяснение:
3(2x-3)+7(1-2x)=1-2(x+4)
6x-9+7-14x=1-2x-8
-8x-2=-7-2x
-8x+2x=-7+2
-6x=-5
x=5/6
Автор ответа:
1
Ответ:6x-9+7-14x=1-2x-8
-8x-2=-2x-7
-8x+2x=2-7
-6x=-5
x=5/6
Объяснение:
Похожие вопросы
Предмет: Українська мова,
автор: nastin0509
Предмет: Русский язык,
автор: успешной
Предмет: Математика,
автор: ЗаяцМим05
Предмет: Английский язык,
автор: olenchenko04
Предмет: Русский язык,
автор: Здоровье09